ANALISIS FAKTOR MAKROEKONOMI YANG MEMPENGARUHI INFLASI DI INDONESIA - Liwa’ul Hamdi; Wardiyanta (JIDE : Journal Of International Development Economics, 2025)
This study aims to analyze the influence of macro economic factors on inflation in Indonesia. The variables examined include exports, imports, foreign exchange reserves, central bank interest rates, exchange rates, and economic growth. The study uses time-series data obtained from the Indonesian Central Bureau of Statistics (BPS) and the World Bank. The analysis was conducted using the Vector Error Correction Model (VECM) to identify both short-run and long-run relationships among the variables. The results indicate that exports, imports, foreign exchange reserves, central bank interest rates, and exchange rates have a significant effect on inflation in Indonesia. Meanwhile, economic growth shows an inverse relationship with inflation, indicating that higher economic growth tends to be associated with lower inflation rates. These findings suggest that inflation stability is influenced by various interconnected macroeconomic indicators, which play an important role in the formulation and implementation of national economic policies.